The Entrepreneurial Intentions Analysis during COVID-19 Pandemic: A Case Study on Graduates of the Faculty of Economics and Business, Widyagama University Malang - Hanif Rani Iswari; Choirul Anam; Ery Tri Djatmika Rudijanto Wahju Wardhana (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The research objective was to analyze the entrepreneurial intentions of FEB graduates at Widyagama University Malang during the Covid-19 pandemic, namely 2019 -2021 through the factor of entrepreneurship education. In addition, the entrepreneurial orientation in this case mediates the relationship between the two. The novelty of this study emphasizes the moderating role of Hofstede's culture on the role of entrepreneurship education and entrepreneurial intentions. This quantitative study used a sampling technique, namely purposive sampling, and distributed questionnaires to 85 respondents. The findings of this study concern the significance found in the interaction between entrepreneurship education on entrepreneurial orientation but not entrepreneurial intention. Entrepreneurial orientation in this case mediates the role of entrepreneurship education in increasing entrepreneurial intentions. Therefore, especially in this new normal, entrepreneurship education is important to direct prospective graduates to have an entrepreneurial orientation so that prospective graduates have confidence in choosing a career as an entrepreneur. Another finding, Hofstede's culture is not a moderator on the interaction of entrepreneurship education and entrepreneurial intentions. Social change after the Covid-19 pandemic has allowed the culture to find suitable forms for development that are compatible with entrepreneurship education in tertiary institutions.